Perbaikan Tata Letak Fasilitas dan Pola Aliran Material pada Usaha Kecil Menengah dengan Metode Triangular Flow Diagram - Dessi Mufti (Universitas Katolik Parahyangan, 2023)
Plant layout is a very important factor in the performance of production process, that is to lean and smooth the production line. A good plant layout is characterized by smooth and lean flow pattern of material movement with minimal distance between departments or workstations. The shorter the distance of material movement, the smaller the material handling cost in the factory. In addition, the efficiency of using the space available in the factory is also the character of a good plat layout and production facilities. During the Covid-19 pandemic, the layout management in a factory must also consider the implementation of the health protocols that have been set. This research aims to re-layout the plat layout of a factory by manage the flow of material that considering social and physical distancing during the Covid-19 pandemic. It is conducted by using Triangular Flow Diagram Method and the distance measurement is carried out using Rectilinear Method. This research is a case study at PT. Citra Nusantara Mandiri (CNM). This company is a Micro, Small and Medium Enterprise (MSMEs) that produces hybrid corn seeds. From the evaluation conducted, it was identified that back tracking and not smooth and lean of flow of material happened in the production process in this company. The findings of the research show that the application of Triangular Flow Diagram Method caused a reduction in the distance of material movement by 48,5% from in the initial conditions. Moreover, the material flow pattern was in the form of a U-Shape.